UF/IFAS Analytical Services Laboratories (ANSERV Labs): Analytical Procedures and Training Manual - Rao S. Mylavarapu; Nancy Wilkinson; Yvens Jean (EDIS, 2024)
The UF/IFAS Analytical Services Laboratories (ANSERV labs) have been in operation, under slightly different names, for nearly 70 years. Since 2008, the ANSERV Labs have been reorganized to accomplish specific research and cooperative extension service missions through two sections in each area- Analytical Research (ARL) and NELAC Certified Environmental Water Quality Labs (EWQL) for all researchers and students and Extension Soil Testing (ESTL) and Livestock Waste Testing Labs (LWTL) for all citizens and agencies of Florida.  The procedures described in this manual reflect the current methodologies for agricultural testing offered by the UF/IFAS Extension Soil Testing Laboratory (ESTL), the Livestock Waste Testing Laboratory (LWTL), the Analytical Research Laboratory (ARL), and the Environmental Water Quality Laboratory (EWQL). This Circular replaces previous information that is contained in other UF/IFAS publications.